ANALISIS KOMUNIKASI KRISIS PEMERINTAH PUSAT REPUBLIK INDONESIA (RI) DALAM MENGATASI KRISIS MINYAK GORENG - R. Firdaus Wahyudi; Suriati Suriati (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2022)
This research aimed to explain about the strategies of crisis communication used by central Government of RI in resolving cooking oil either related to scarcity or price increase of cooking oil. This research is study of library research based on selected online news and President of RI, Joko widodo posts on his social media, Twitter. In this study revealed that there were various strategy of crisis communication implemented by central government of RI in resolve the crisis of cooking oil such as; by doing inspection to field directly to ensured the price or stock of cooking oil; giving instruction to the trade minister to issued regulations due to governance of cooking oil; policy to subsidy and cash transfers for cooking oil; and also cabinet reshuffle policy for the trade minister position in order to enhanced the central government efforts to resolve such cooking oil crisis.